High-performance copper sa acid additive and preparation process thereof

CN120925036BActive Publication Date: 2026-09-15GUANGZHOU HKS SURFACE TREATMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511122489.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2026-09-15
Estimated Expiration
2045-08-12

AI Technical Summary

Technical Problem

焦磷酸盐镀铜主要用于电铸件的敷涂,锌、铝或其合金镀铜及不锈钢印膜、冲膜的镀铜,焦磷酸盐镀铜对镀件表面的状况要求不高,镀液为碱性,腐蚀性小,但其电镀过程控制困难,废液的处理较酸铜电镀困难,使用已受到限制

Benefits of technology

本发明通过咪唑溴盐离子液体和端羟基支化聚醚协同,细化晶粒形成更加致密的微观结构,提高镀层的致密性,降低镀层孔隙率,提升镀层与镀件的结合力。而且咪唑溴盐离子液体的添加可以提高镀液的导电率,有利于提升铜的沉积速率,在短时间内形成均匀的晶核,有利于形成高附着力且分布均匀的沙面镀层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120925036B_ABST
    Figure CN120925036B_ABST
Patent Text Reader

Abstract

The application discloses a high-performance sand acid copper additive and a preparation process thereof, and belongs to the technical field of electroplating. The high-performance sand acid copper additive comprises imidazole bromide salt ionic liquid and hydroxyl-terminated branched polyether. The imidazole bromide salt ionic liquid is prepared through nucleophilic substitution of alkyl imidazole and bromoalkane. The hydroxyl-terminated branched polyether is prepared through ring-opening polymerization of glycidol and propylene oxide under the action of a catalyst, with a trihydric alcohol as a starting raw material. The imidazole bromide salt ionic liquid and the hydroxyl-terminated branched polyether are synergized, the crystal grains are refined, the microstructure is more compact, the compactness of the plating layer is improved, the porosity of the plating layer is reduced, and the adhesion between the plating layer and the plated part is improved. The sand copper plating layer obtained is uniform in color, delicate in sand feeling, fine in plating layer, uniform in thickness, low in internal stress, has a good decorative effect, and has a good market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electroplating technology, specifically relating to a high-performance copper succinate additive and its preparation process. Background Technology

[0002] Copper is a tough and malleable metal with excellent ductility, good electrical and thermal conductivity, and low porosity. Electroplated copper layers are widely used in the field of electronic information products due to their excellent electrical and thermal conductivity and mechanical ductility. Copper plating technology has thus permeated the entire field of electronic materials manufacturing, from printed circuit board (PCB) manufacturing to IC packaging and copper interconnect technology for large-scale integrated circuits (chips). Therefore, copper plating technology has become one of the essential electroplating technologies in modern electronic manufacturing.

[0003] There are three commonly used copper plating solutions: cyanide plating solution, acidic sulfate plating solution, and pyrophosphate plating solution. Cyanide copper plating is mainly used as a base layer in decorative electroplating. It has strong depth-deepening capabilities, but its biggest drawback is the high toxicity of the plating solution, which places extremely high demands on process monitoring and wastewater treatment. Pyrophosphate copper plating is mainly used for coating electroformed parts, copper plating of zinc, aluminum, or their alloys, and copper plating for stainless steel printing and stamping. Pyrophosphate copper plating has less stringent requirements on the surface condition of the parts being plated, and the plating solution is alkaline with low corrosiveness. However, its electroplating process is difficult to control, and wastewater treatment is more difficult than with acid copper plating, thus its use is limited. The most commonly used copper plating solution system is the acidic copper sulfate bright copper plating system. Because its basic components are simple, the solution is stable, and the current efficiency is high, with the addition of appropriate brighteners, a coating with high gloss, high leveling, and high uniformity can be obtained. Moreover, the acidic sulfate copper plating process is easy to maintain and operate. Therefore, it has replaced the pyrophosphate copper plating process in industry and has been widely used. In addition, there are some occasions where a matte, sand-finish decorative effect is required, so the sand-finish copper plating process has been developed. Summary of the Invention

[0004] The purpose of this invention is to provide a high-performance copper tartar additive and its preparation process to provide a matte, sandblasted surface decorative effect.

[0005] The objective of this invention can be achieved through the following technical solutions: The first aspect of this application provides a high-performance copper succinate additive, which includes an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether, wherein the mass ratio of the imidazole bromide ionic liquid to the hydroxyl-terminated branched polyether is 10:5-8.

[0006] The imidazole bromide ionic liquid is prepared by nucleophilic substitution of alkyl imidazole and bromoalkane. Bromine ions can be adsorbed on the surface between the coated parts through covalent bonding. The imidazole cations in the imidazole bromide ionic liquid interact with the bromide ions to form hydrogen bonds. The imidazole bromide ionic liquid will be adsorbed on the active sites of copper deposition, inhibiting crystal growth and causing the coating to form fine and disordered grains, resulting in enhanced surface light scattering and a macroscopic matte finish.

[0007] During the reduction of copper ions, the length of the nonpolar groups hinders the reduction process, and this hindrance increases with the increase of the length of the nonpolar groups in the imidazole bromide ionic liquid, which helps to form small-diameter grains.

[0008] Hydroxyl-terminated branched polyethers are prepared by ring-opening polymerization of triols with glycidyl ether and propylene oxide under the action of a catalyst. The hydroxyl-terminated branching polymerization forms a nanoscale uneven structure on the coating surface through the co-deposition or adsorption of non-conductive microparticles. This structure reduces surface gloss by scattering light rather than specular reflection. The hydroxyl-terminated branched polyether can form nanoscale pores in the coating, promoting the "anchoring effect" of copper grains and improving the bonding strength with the substrate. The hydroxyl-terminated branched polyether has high steric hindrance, making it easier for subsequent copper deposition to cover the adsorption on the cathode surface, reducing the weak boundary layer at the interface. In contrast, linear polymers such as linear polyethylene glycol tend to form long chain entanglements, resulting in a higher risk of residue and hindering the improvement of the adhesion between the coating and the plated part.

[0009] The copper coating obtained by imidazole bromide ionic liquid combined with terminal hydroxyl branched polyether is rough and has a uniform particle distribution. The matte surface may enhance the mechanical bonding with the substrate or subsequent coating due to the larger surface area. However, if the roughness is too high (such as too many dendrites or pores), it may reduce the bonding force.

[0010] This invention utilizes the synergistic effect of imidazole bromide ionic liquid and hydroxyl-terminated branched polyether to refine grains, forming a denser microstructure, improving the density of the coating, reducing its porosity, and enhancing the adhesion between the coating and the workpiece. Furthermore, the addition of imidazole bromide ionic liquid increases the conductivity of the plating solution, which is beneficial for increasing the copper deposition rate and forming uniform crystal nuclei in a short time, thus facilitating the formation of a highly adhesive and uniformly distributed matte-finish coating.

[0011] Furthermore, the molar ratio of alkylimidazolium to bromoalkane is 1:1.1-1.2.

[0012] Further, the bromoalkane is nonane bromo; the alkyl imidazole is one of N-hexadecylimidazolium, 1-octylimidazolium, 2-butylimidazolium, 1-propylimidazolium, and N-methylimidazolium.

[0013] Furthermore, the amount of catalyst added is 0.05% to 0.06% of the total amount of triol, glycidyl ether and propylene oxide, and the molar ratio of triol, glycidyl ether and propylene oxide is 1:18:3-1.

[0014] Furthermore, the triol is one of 1,3,5-tris(2-hydroxyethyl)cyanuric acid and 1,1,1-trimethylolpropane.

[0015] Furthermore, the amount of the high-performance copper succinate additive added to the basic electrolyte is 300-400 mg / L.

[0016] Furthermore, the basic electrolyte composition uses water as a solvent, with copper sulfate at 180-220 g / L, sulfuric acid at 50-70 g / L, and chloride ions at 60-150 mg / L.

[0017] Furthermore, a preparation process for a high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkyl imidazole and bromoalkanes were added to ethanol, and the temperature was set at 78°C. The mixture was refluxed for 6-24 hours. After the reaction was completed, the ethanol was removed by vacuum distillation, and the mixture was recrystallized with anhydrous diethyl ether to obtain an imidazole bromide ionic liquid.

[0018] Under nitrogen protection, triol and catalyst are added to a reaction vessel and mixed. Then glycidyl ether and propylene oxide are added. The mixture is stirred at 130-140°C for 70-80 minutes. After the reaction is completed, unreacted monomers are removed by vacuum concentration to obtain hydroxyl-terminated branched polyether.

[0019] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether.

[0020] The beneficial effects of this invention are: This invention utilizes the synergistic effect of imidazole bromide ionic liquid and hydroxyl-terminated branched polyether to refine grains, forming a denser microstructure, improving the density of the coating, reducing its porosity, and enhancing the adhesion between the coating and the workpiece. Furthermore, the addition of imidazole bromide ionic liquid increases the conductivity of the plating solution, which is beneficial for increasing the copper deposition rate and forming uniform crystal nuclei in a short time, thus facilitating the formation of a highly adhesive and uniformly distributed matte-finish coating.

[0021] The high-performance copper tarnish additive of this invention produces a copper tarnish coating with uniform color, fine sandy texture, fine coating, uniform thickness, and low internal stress, resulting in a good decorative effect and promising market application prospects. Attached Figure Description

[0022] The invention will now be further described with reference to the accompanying drawings.

[0023] Figure 1This is a comparison chart of the performance of the high-performance copper succinate additive prepared in Example 1 of this invention and a commercially available bright coating. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] The following is a detailed description of a high-performance copper succinate additive and its preparation process according to an embodiment of this application.

[0026] In the examples and comparative examples, the basic electrolyte composition was based on water as the solvent, with 180-220 g / L copper sulfate, 50-70 g / L sulfuric acid, and 60-150 mg / L chloride ions. The amount of high-performance copper succinate additive added was 300-400 mg / L.

[0027] The electroplating conditions are as follows: constant current dual-anode electroplating is used, with a distance of 6-25 cm between the cathode and anode, a current density of 1.5-6 amperes / dm², and a temperature of 20-30℃. The electroplating time is 30-60 minutes; phosphor bronze is used as the anode, and the cathode is moved and / or agitated with air.

[0028] The following is a detailed description with reference to specific examples.

[0029] Example 1 This embodiment provides a high-performance copper succinate additive, which comprises an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether; the preparation process of this high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkylimidazolium and bromoalkane were added to ethanol, and the mixture was refluxed at 78°C for 24 hours. After the reaction was completed, the ethanol was removed by vacuum distillation, and the product was recrystallized from anhydrous diethyl ether to obtain an imidazolium bromide ionic liquid. The molar ratio of alkylimidazolium to bromoalkane was 1:1.1. The bromoalkane was nonane bromoalkane; the alkylimidazolium was N-hexadecylimidazolium.

[0030] Under nitrogen protection, triol and DMC catalyst (bimetallic cyanide complex catalyst) were added to a reactor and mixed. Then, glycidyl ether and propylene oxide were added, and the mixture was stirred at 130°C for 70 min. After the reaction, unreacted monomers were removed by vacuum concentration to obtain hydroxyl-terminated branched polyether. The catalyst addition amount was 0.05% of the total amount of triol, glycidyl ether, and propylene oxide, and the molar ratio of triol, glycidyl ether, and propylene oxide was 1:18:2. The triol was 1,3,5-tris(2-hydroxyethyl)cyanuric acid.

[0031] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether, wherein the mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:5.

[0032] Example 2 This embodiment provides a high-performance copper succinate additive, which comprises an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether; the preparation process of this high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkylimidazolium and bromoalkane were added to ethanol, and the mixture was refluxed at 78°C for 20 h. After the reaction was completed, the ethanol was removed by vacuum distillation, and the product was recrystallized from anhydrous diethyl ether to obtain an imidazolium bromide ionic liquid. The molar ratio of alkylimidazolium to bromoalkane was 1:1.1. The bromoalkane was nonane bromoalkane; the alkylimidazolium was 1-octylimidazolium.

[0033] Under nitrogen protection, triol and DMC catalyst (bimetallic cyanide complex catalyst) were added to a reactor and mixed. Then, glycidyl ether and propylene oxide were added, and the mixture was stirred at 130°C for 70 min. After the reaction, unreacted monomers were removed by vacuum concentration to obtain hydroxyl-terminated branched polyether. The catalyst addition amount was 0.05% of the total amount of triol, glycidyl ether, and propylene oxide, and the molar ratio of triol, glycidyl ether, and propylene oxide was 1:18:2. The triol was 1,3,5-tris(2-hydroxyethyl)cyanuric acid.

[0034] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether, wherein the mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:5.

[0035] Example 3 This embodiment provides a high-performance copper succinate additive, which comprises an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether; the preparation process of this high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkylimidazolium and bromoalkane were added to ethanol, and the mixture was refluxed at 78°C for 18 hours. After the reaction was completed, the ethanol was removed by vacuum distillation, and the product was recrystallized from anhydrous diethyl ether to obtain an imidazolium bromide ionic liquid. The molar ratio of alkylimidazolium to bromoalkane was 1:1.1. The bromoalkane was nonane bromoalkane; the alkylimidazolium was 2-butylimidazolium.

[0036] Under nitrogen protection, triol and DMC catalyst (bimetallic cyanide complex catalyst) were added to a reactor and mixed. Then, glycidyl ether and propylene oxide were added, and the mixture was stirred at 130°C for 70 min. After the reaction, unreacted monomers were removed by vacuum concentration to obtain hydroxyl-terminated branched polyether. The catalyst addition amount was 0.05% of the total amount of triol, glycidyl ether, and propylene oxide, and the molar ratio of triol, glycidyl ether, and propylene oxide was 1:18:2. The triol was 1,3,5-tris(2-hydroxyethyl)cyanuric acid.

[0037] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether, wherein the mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:5.

[0038] Example 4 This embodiment provides a high-performance copper succinate additive, which comprises an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether; the preparation process of this high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkylimidazolium and bromoalkane were added to ethanol, and the mixture was refluxed at 78°C for 14 hours. After the reaction was completed, the ethanol was removed by vacuum distillation, and the product was recrystallized from anhydrous diethyl ether to obtain an imidazolium bromide ionic liquid. The molar ratio of alkylimidazolium to bromoalkane was 1:1.1. The bromoalkane was nonane bromoalkane; the alkylimidazolium was N-methylimidazolium.

[0039] Under nitrogen protection, triol and DMC catalyst (bimetallic cyanide complex catalyst) were added to a reactor and mixed. Then, glycidyl ether and propylene oxide were added, and the mixture was stirred at 130°C for 70 min. After the reaction, unreacted monomers were removed by vacuum concentration to obtain hydroxyl-terminated branched polyether. The catalyst addition amount was 0.05% of the total amount of triol, glycidyl ether, and propylene oxide, and the molar ratio of triol, glycidyl ether, and propylene oxide was 1:18:2. The triol was 1,3,5-tris(2-hydroxyethyl)cyanuric acid.

[0040] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether, wherein the mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:5.

[0041] Example 5 This embodiment provides a high-performance copper succinate additive, which comprises an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether; the preparation process of this high-performance copper succinate additive includes the following steps: Under a nitrogen atmosphere, alkylimidazolium and bromoalkane were added to ethanol, and the mixture was refluxed at 78°C for 24 hours. After the reaction was completed, the ethanol was removed by vacuum distillation, and the product was recrystallized from anhydrous diethyl ether to obtain an imidazolium bromide ionic liquid. The molar ratio of alkylimidazolium to bromoalkane was 1:1.1. The bromoalkane was nonane bromoalkane; the alkylimidazolium was N-hexadecylimidazolium.

[0042] Under nitrogen protection, triol and DMC catalyst (bimetallic cyanide complex catalyst) were added to a reactor and mixed. Then, glycidyl ether and propylene oxide were added, and the mixture was stirred at 130°C for 70 min. After the reaction, unreacted monomers were removed by vacuum concentration to obtain hydroxyl-terminated branched polyether. The amount of catalyst added was 0.05%–0.06% of the total amount of triol, glycidyl ether, and propylene oxide, and the molar ratio of triol, glycidyl ether, and propylene oxide was 1:18:2. The triol was one of 1,1,1-trimethylolpropane.

[0043] A high-performance copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether, wherein the mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:5.

[0044] Example 6 This embodiment provides a high-performance copper succinate additive. The difference between this embodiment and Example 1 is that the ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is different. The mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:7.

[0045] Example 7 This embodiment provides a high-performance copper succinate additive. The difference between this embodiment and Example 1 is that the ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is different. The mass ratio of imidazole bromide ionic liquid to hydroxyl-terminated branched polyether is 10:8.

[0046] Comparative Example 1 Compared with Example 1, this comparative example does not add imidazole bromide ionic liquid, but the other raw materials and preparation process are the same as in Example 1.

[0047] Comparative Example 2 Compared with Example 1, this comparative example does not contain terminal hydroxyl branched polyether, but the other raw materials and preparation process are the same as in Example 1.

[0048] Comparative Example 3 Compared with Example 1, this comparative example replaces the terminal hydroxyl branched polyether with polyethylene glycol 6000. Comparative Example 4 Compared with Example 1, the comparative example uses an imidazole bromide ionic liquid and terminal hydroxyl branched polyether in a mass ratio of 1:1.5, while the remaining raw materials and preparation process remain the same as in Example 1.

[0049] Test case The additives prepared in Examples 1-7 and Comparative Examples 1-3 were tested. Electroplating pretreatment: The treatment sequence for stainless steel sheets is as follows: pure water cleaning → polishing with 1000-grit sandpaper → polishing with 2000-grit sandpaper → pure water cleaning → acetone degreasing → pure water cleaning → immersion in 10% HCl for 8-10 seconds to activate the surface → pure water cleaning.

[0050] Copper plating: The basic electrolyte used in Examples 1-7 and Comparative Examples 1-3 consisted of water as the solvent, 200 g / L copper sulfate, 70 g / L sulfuric acid, and 100 mg / L chloride ions. The amount of high-performance copper succinate additive added was 300 mg / L. Comparative Example 5 was also included, with the amount of high-performance copper succinate additive added at 700 mg / L.

[0051] The electroplating conditions are as follows: constant current dual-anode electroplating is used, the distance between the cathode and anode is 15 cm, the current density is 3 amperes / square decimeter, and the temperature is 20-30℃. Phosphor bronze is used for the anode, and the cathode is moved and / or agitated with air.

[0052] After copper plating: rinse with water → dry with cold air → test the plating layer. Record the plating time and plating thickness data.

[0053] The comparison between the performance of the high-performance copper succinate additive prepared in Example 1 and commercially available bright coatings is shown in the figure below. Figure 1 As shown.

[0054] Scratch test: Testing the coating performance after 30 minutes of electroplating: The scratch test was conducted using a 30-meter-long scribing line. o The hard steel scribing tool is used to scribing two parallel lines with a spacing of about 2 mm. When scribing the two parallel lines, sufficient pressure is applied so that the scribing line passes through the coating and cuts into the base metal in one stroke. If any part of the coating between the lines peels off from the base metal, the coating fails the test.

[0055] The results are shown in Table 1: Table 1 As shown in Table 1 and compared with Examples 1-4, the surface tension of the electroplating solution decreases with the increase of the length of the nonpolar groups in the imidazole bromide ionic liquid. This decrease in surface tension helps the electroplating solution spread better on the surface of the workpiece, reduces the aggregation of the solution on the surface and the adhesion of bubbles, and allows copper ions to be more evenly distributed on the surface of the workpiece, which is beneficial for rapid copper deposition. The hydroxyl-branched polyether added in Example 5 can promote the "anchoring effect" of copper grains and improve the bonding strength with the substrate.

[0056] Based on the comparison of Example 1 and Comparative Examples 1-2, it can be seen that in Comparative Example 1, the absence of imidazole bromide ionic liquid reduces the conductivity of the plating solution. In Comparative Example 2, the absence of terminal hydroxyl branched polyether affects the bonding strength between copper grains and the plated parts, reduces the formation speed of the plating layer, and affects the quality of the plating layer. In Comparative Example 3, replacing the terminal hydroxyl branched polyether with linear polyethylene glycol has a relatively small impact on the formation efficiency of the plating layer, but the bonding strength between the plating layer and the plated parts is poor. In Comparative Example 4, the excessive addition of terminal hydroxyl branched polyether, and in Comparative Example 5, the increased proportion of imidazole bromide ionic liquid and terminal hydroxyl branched polyether in the electroplating solution, also affect the formation efficiency of the plated parts and the quality of the plating layer.

[0057] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0058] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A copper succinate additive, characterized in that, It includes an imidazole bromide ionic liquid and a hydroxyl-terminated branched polyether, wherein the mass ratio of the imidazole bromide ionic liquid to the hydroxyl-terminated branched polyether is 10:5-8. The imidazole bromide ionic liquid is prepared by nucleophilic substitution of alkyl imidazole and bromoalkane; The terminal hydroxyl branched polyether is prepared by ring-opening polymerization of triol with glycidyl ether and propylene oxide under the action of a catalyst. The bromoalkane is nonane bromo; the alkyl imidazole is one of N-hexadecylimidazolium, 1-octylimidazolium, 2-butylimidazolium, 1-propylimidazolium, and N-methylimidazolium.

2. The copper succinate additive according to claim 1, characterized in that, The molar ratio of alkylimidazolium to bromoalkane is 1:1.1-1.

2.

3. The copper succinate additive according to claim 1, characterized in that, The catalyst is a bimetallic cyanide complex catalyst; the amount of catalyst added is 0.05% to 0.06% of the total amount of triol, glycidyl ether and propylene oxide.

4. The copper succinate additive according to claim 1, characterized in that, The molar ratio of triol, glycidyl ether, and propylene oxide is 1:18:3-1.

5. The copper succinate additive according to claim 1, characterized in that, The triol is one of 1,3,5-tris(2-hydroxyethyl)cyanuric acid and 1,1,1-trimethylolpropane.

6. The copper succinate additive according to claim 1, characterized in that, The amount of copper succinate additive added to the basic electrolyte is 300-400 mg / L.

7. The copper succinate additive according to claim 6, characterized in that, The basic electrolyte uses water as a solvent and includes 180-220 g / L copper sulfate, 50-70 g / L sulfuric acid, and 60-150 mg / L chloride ions.

8. A preparation process for a copper succinate additive, used to prepare the copper succinate additive according to any one of claims 1-7, characterized in that, Includes the following steps: Under a nitrogen atmosphere, alkyl imidazole and bromoalkanes were added to ethanol for a nucleophilic substitution reaction. After the reaction, the ethanol was removed by vacuum distillation, and the mixture was recrystallized with anhydrous diethyl ether to obtain an imidazole bromide ionic liquid. Under nitrogen protection, triol and catalyst are added to a reaction vessel and mixed. Then glycidyl ether and propylene oxide are added to initiate a ring-opening polymerization reaction. After the reaction is completed, unreacted monomers are removed by vacuum concentration to obtain terminal hydroxyl branched polymer. Copper succinate additive is obtained by mixing imidazole bromide ionic liquid and hydroxyl-terminated branched polyether.

9. The preparation process of a copper succinate additive according to claim 8, characterized in that, The temperature range for nucleophilic substitution reactions is 78-80℃, and the reaction time is 6-24h. The temperature range for the ring-opening polymerization reaction is 130-140℃, and the reaction time is 70-80 min.

Citation Information

Patent Citations

  • Preparation method for allyl-terminated hyperbranched polyether polyol

    CN106554494A

  • Additive for electroplating copper, preparation method of additive and electroplating solution

    CN119040975A